2010
DOI: 10.1016/j.bandc.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine consumption enhances the executive control of visual attention in habitual consumers

Abstract: a b s t r a c tRecent work suggests that a dose of 200-400 mg caffeine can enhance both vigilance and the executive control of visual attention in individuals with low caffeine consumption profiles. The present study seeks to determine whether individuals with relatively high caffeine consumption profiles would show similar advantages. To this end, we examined the effects of four caffeine doses (0 mg, 100 mg, 200 mg, 400 mg) on low-and high-level visual attention in individuals with high consumption profiles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 81 publications
7
59
2
2
Order By: Relevance
“…Although it is unknown whether theanine consumption leads to habituation, habitual caffeine consumption results in increased tolerance for its stimulating properties and withdrawal effects upon cessation of intake (James and Rogers 2005). Relevant to the present study, in previous work, caffeine enhanced executive function on the ANT and detection for global errors on a language-based task beginning at 200 mg caffeine in low habitual caffeine consumers and 400 mg caffeine in high habitual caffeine consumers (Brunyé et al 2010a(Brunyé et al , 2010b(Brunyé et al , 2012. Additionally, a global processing bias was evident on the hierarchical shape task after 100 mg caffeine in low habitual caffeine consumers (Mahoney et al 2011).…”
Section: Limitationssupporting
confidence: 62%
See 3 more Smart Citations
“…Although it is unknown whether theanine consumption leads to habituation, habitual caffeine consumption results in increased tolerance for its stimulating properties and withdrawal effects upon cessation of intake (James and Rogers 2005). Relevant to the present study, in previous work, caffeine enhanced executive function on the ANT and detection for global errors on a language-based task beginning at 200 mg caffeine in low habitual caffeine consumers and 400 mg caffeine in high habitual caffeine consumers (Brunyé et al 2010a(Brunyé et al , 2010b(Brunyé et al , 2012. Additionally, a global processing bias was evident on the hierarchical shape task after 100 mg caffeine in low habitual caffeine consumers (Mahoney et al 2011).…”
Section: Limitationssupporting
confidence: 62%
“…However, these doses were sufficient to affect executive function. Caffeine consumption resulted in the expected improvement in executive function (Brunyé et al 2010a(Brunyé et al , 2010b. In contrast, theanine prior to an emotionally arousing experience resulted in decrements in executive function, potentially related to its anxiolytic properties.…”
Section: Attentionmentioning
confidence: 97%
See 2 more Smart Citations
“…Brain activity difference and behavioral measure difference between pre-and postcaffeine sessions were not correlated with each other either. No caffeine-induced behavior changes found in this study were consistent with an early study of caffeine in sustained attention (41) and a more recent study (42), although significant beneficial behavioral effects of caffeine were observed in several other studies (43,44). One reason for no behavior change after caffeine might be due to the fact that the amount of caffeine (200 mg) used in this study was not enough to cause observable behavior difference.…”
Section: Discussionsupporting
confidence: 89%